Examination of huntington’s disease with atypical clinical features in a Bangladeshi family tree and study of association of miRNAs expression level with the diseased condition - Khan, Tanzila (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfillment of the requirement for the degree of B.Sc in Microbiology, 2016.